News Translation and Translation Ethics in the Cypriot Context - Floros, Georgios (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
In news translation, some of the most prominent issues still debated on concern news translation as gatekeeping, the application of traditional models and the issue of the very definition of translation itself. Within this context, this paper will focus on the use of translation in news production in the Cypriot context. Data from Cypriot newspapers and the Cypriot Press and Information Office (PIO) point to the assumption that translation is used for disseminating national policy in ways which might stand in a conflicting relationship with issues pertaining to translation ethics. While news reporting is almost by necessity a carrier of national ideology, the same cannot be assumed automatically for material which is translated. The ultimate aim is to show how national ideologies violate the desired informativity of news and to challenge the ethical ‘‘uniformity’’ observed between news reporting and news translation, in favor of a higher ethical awareness on the part of journalists and newspapers. The underlying premise of the article is that news translation could perhaps be treated according to the same ethical considerations as translation in the conventional sense, despite the recontextualization and filtering of the content expressed.